Web 2.0 Socail Network Sites And Facebook Marketing - Andreas Chang (Binus Business Review, 2011)
The use of Web 2.0 and Social Network Sites (SNS) has become an amazing phenomenon. In fact, one of the fastest-growing arenas of the World Wide Web is the space of so-called social networking sites. Face book, Tweeter, MySpace and other Social Network Sites have huge population of users. Almost seven hundred million people use Facebook, and hundreds of million others use other social networking sites. More and more advertisers switch their marketing budget to these SNS. This study contributes to our understanding of the Web 2.0 and the use of social networking websites by examining available literature. It seeks to understand what Web 2.0 and SNS mean, the trends, its functions and how they can be leveraged for marketing purposes.